Three major handbooks in three years: Stylistics as a mature discipline. (August 2016) - Sorlin, Sandrine
This review article brings to the fore what the publication of three handbooks in major publishing houses in the past three years ( The Routledge Handbook of Stylistics, The Cambridge Handbook of Stylistics and The Bloomsbury Companion to Stylistics ) can reveal about the state of stylistics in 2016. After depicting the specific character of each volume, the article highlights the way old theoretical models in stylistics are re-exploited in innovative ways and gives prominence to new theories and perspectives that have developed rigorous methodologies and proper purposes. It also makes apparent how the volumes both explicitly and implicitly perceive the field of stylistics as regards its scope and frontiers, the extent of its corpora and its relation with other close disciplines. If it inherently welcomes interdisciplinary collaborations, it yet seems to do so without adulterating its primary concern for language. The three handbooks show that stylistics has entered its prime as a discipline. Yet although it has become a self-assured field, it remains uncompromisingly open to criticism and debate as reflected in some chapters. The last sub-section is devoted to the future prospects of stylistics in terms of the promising research paths the discipline is currently taking.